Penatalaksanaan Fisioterapi pada Diabetic Peripheral Neuropaty (DPN) pada Pasien dengan Kasus Diabetes Militus Tipe II: A Case Report - Demma Taufan Duwa (Nur Science Institute, 2021)
Background Diabetic Peripheral Neuropathy (DPN) is a symptom experienced in most cases of Type II Diabetes Mellitus. Which causes sensory disturbances such as pain sensations, numbness, burning sensations, and even can cause decreased muscle strength and balance disorders. Symptoms of DPN occur in 2/3 of cases of DM. This case report aims to present a physiotherapy management strategy in Diabetic Peripheral Neuropathy. Case description, of a 70 year old woman with a medical diagnosis of Diabetic Peripheral Neuropathy. The patient complained of burning sensation along the legs and numbness in the soles of the feet, especially in the right leg. The physiotherapist met with the patient 3 times. Result: The results of the evaluation for 3 treatments showed that there were changes in aspects of neuropathy, dynamic balance, lower extremity muscle strength, and burning sensation and numbness. For the patient's static balance aspect, there was no decrease in the level of static balance. In addition to the range of motion (ROM) of the lower extremities, there are no complaints. Discussion: Physiotherapy interventions are very beneficial for patients with Diabetic Peripheral Neuropathy. Although, the process of peripheral nerve recovery takes a long time, physiotherapy intervention can minimize the symptoms resulting from Diabetic Peripheral Neuropathy. Further research is needed to determine the importance of physiotherapy in the condition of Diabetic Peripheral Neuropathy.